2018
DOI: 10.1002/casp.2344
|View full text |Cite
|
Sign up to set email alerts
|

“It's ok if it's hidden”: The discursive construction of everyday racism for refugees and asylum seekers in Wales

Abstract: Wales has a long history of migration; however, the introduction of dispersed asylum seekers in 2001 has led to Wales becoming a more superdiverse nation. Wales has often been positioned as a more “tolerant nation” than England; however, the increasingly superdiverse nature of Wales in a postdevolution era may now be calling this tolerance thesis into question. Models of refugee and asylum seeker integration suggest that the absence of racism plays a key role in integration. This paper reports the findings of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…A number of discursive studies (Goodman et al, 2014;Kirkwood, Goodman, McVittie, & McKinlay, 2015;Parker, 2018) suggest that asylum seekers avoid making direct criticisms of the host country so as not to appear ungrateful for the support they have been given in the host country. Indeed, there is evidence of each of the participants' talk functioning in a similar way here, as they present themselves as grateful for the support they have received and focus on their responsibilities and ability to contribute to the economy or society rather than rely purely on state help.…”
Section: Discussionmentioning
confidence: 99%
“…A number of discursive studies (Goodman et al, 2014;Kirkwood, Goodman, McVittie, & McKinlay, 2015;Parker, 2018) suggest that asylum seekers avoid making direct criticisms of the host country so as not to appear ungrateful for the support they have been given in the host country. Indeed, there is evidence of each of the participants' talk functioning in a similar way here, as they present themselves as grateful for the support they have received and focus on their responsibilities and ability to contribute to the economy or society rather than rely purely on state help.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, difficulties reporting harassment contribute to the prevalence of sexual harassment. Research has shown that targets of systemic problematic behavior, such as sexism and racism, find it extremely troublesome to report such instances or fashion them so that they are accepted by others (Louw‐Potgeiter, 1989; Parker, 2018; Shelton & Stewart, 2004). For instance, complaints about sexual harassment can be recast as those about uncivil or unprofessional behavior (Shelton & Stewart, 2004).…”
Section: Sexual Harassmentmentioning
confidence: 99%
“…One occasion in which experience, or ‘knowledge, feelings, emotions, thoughts, understandings’ and so on, ‘become live’ is when people talk about it. Yet, talking about experiences (of racism) is an intricate business, as illustrated in Goodman et al's (2014) interview study with refugees and asylum seekers in the United Kingdom (also in Kirkwood et al, 2013; Parker, 2018). This intricacy is elevated by racism, which, in Schegloff's (2005, p. 449) terms, is a social problem that involves ‘segments of the population defined by category membership’.…”
Section: Introductionmentioning
confidence: 99%